Devkota’s The Lunatic: A Master Piece of Modern Nepali Literature - Bista, Aishwarya (Journal of Entrepreneurship & Management Studies, 2024)
This study analyzes Laxmi Prasad Devkota’s “The Lunatic” as a master piece of modern Nepali literature. Objective of the study is to examine the key modern literary characteristics of the The Lunatic to exemplify The Lunatic as a master piece of modern literature. “The Lunatic” by Devkota uses modern literary characteristics such as experimentation, stark imagery, individualism, societal change and stream of consciousnesses. These modern poetic styles help the poet in expressing experiences and feelings of the period in the wider cultural context of Nepal moving towards modernity. Qualitative method guided discourse analysis is used to analyze the key modern literary characteristics of The Lunatic.